1993
DOI: 10.1007/bf00025091
|View full text |Cite
|
Sign up to set email alerts
|

Screening sorghum for tolerance to excess manganese in solution culture

Abstract: This study was conducted to define traits to screen sorghum (Sorghum bicolor L. Moench) genotypes for tolerance to excess Mn. Visual Mn toxicity symptoms, net and total root lengths, shoot and root dry matter yields, and shoot and root Mn concentrations were determined for plants grown in nutrient solutions (pH 4.5) at different levels of Mn (0, 3, 6, 9 and 12 mM above the initial 18 ~tM) to assess plant responses to excess Mn. Dry matter yields showed greatest variability among genotypes, and was an effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Information on level of Mn and trait to best assess sorghum genotypes for differences to excess Mn in solution culture has recently been reported (Mgema and Clark, 1994). This study showed that 3.0 and 6.0 mM Mn in solution resulted in good differences among eight sorghum genotypes in response to excess Mn, but 9.0 and 12.0 mM Mn were too high.…”
Section: Introductionmentioning
confidence: 80%
“…Information on level of Mn and trait to best assess sorghum genotypes for differences to excess Mn in solution culture has recently been reported (Mgema and Clark, 1994). This study showed that 3.0 and 6.0 mM Mn in solution resulted in good differences among eight sorghum genotypes in response to excess Mn, but 9.0 and 12.0 mM Mn were too high.…”
Section: Introductionmentioning
confidence: 80%